The impact of the COVID-19 pandemic on cross-border shopping tourism: the case of Hungary - Tömöri, Mihály; Staniscia, Barbara (Hungarian Geographical Bulletin, 2023)
By today the smooth functioning of the global economy has been highly dependent on the uninterrupted flow of factors across borders. The free flow of tourists is also inevitable for the proper functioning of the global tourism industry. However, tourism and various forms of cross-border (tourism) activities were put under unprecedented pressure due to the COVID-19 pandemic, since most countries, including Hungary, introduced serious restrictions on mobility to slow down the spread of the virus. This paper focuses on a relatively under-researched topic, cross-border shopping tourism in the context of the COVID-19 pandemic. Before the outbreak of the pandemic, shopping tourism was deemed to be an increasingly important component of the tourism value chain. Several studies have demonstrated that shopping has become one of the most favourable activities among tourists and one of the major categories of tourists’ expenditure. Based on the review of the relevant literature, the paper introduces the notion and forms of shopping tourism and discusses the major research topics with special regard to the effects of the pandemic and other types of crisis events. The impact of the pandemic on shopping tourism is observed through the example of Hungary, whereby the effects of restrictions, exchange rate fluctuations, and price-level differences on the number of in- and outbound shopping trips, and the related expenditures, are evaluated. Results show that re-bordering processes due to the pandemic have not only resulted in an unprecedented decline in cross-border shopping tourism, but they also contributed to the spatial restructuring of shopping (tourism) and retailing. The pandemic not only sustained cross-border differentials vital to shopping tourism but sometimes even created new forms of them; these differences, however, could not counter the negative effects of restricted international mobility. The paper aims to contribute to the literature on cross-border tourism by reviewing the effects and consequences of COVID-19 and related restrictions on shopping tourism.